Wider determinants of adverse birth outcomes in Birmingham and Solihull - Ellis, David; Au-Yeung, Chung Him; Dallaway, Alexander; Basra, Ranjana; Owusu-Nepaul, Sylvia; Riley, Jenny; Howell-Jones, Rebecca; Varney, Justin; Gibbon, Marion (Frontiers in Public Health, 2025)
IntroductionBirmingham and Solihull face significant challenges related to adverse birth outcomes. This study aimed to identify demographic, socioeconomic, and lifestyle factors associated with an increased risk of low birth weight, premature birth, stillbirth, and neonatal death in Birmingham and Solihull.MethodsBirths (n = 41, 231) between October 2020 and April 2023 were analysed. The attributable fraction of premature births and low birth weight (LBW) attributable to socioeconomic and ethnic inequality was calculated. Multiple logistic regression analyses identified groups that had increased odds of premature birth (n = 3, 312), LBW (n = 1, 197), stillbirth (n = 173), and neonatal death (n = 208).ResultsAttributable fraction analysis estimated that 191 premature births and 211 LBWs each year would not have occurred if all women had the same rates as White women living in the least deprived areas. Ethnicity, socioeconomic deprivation, medical care, lifestyle, and vulnerability status were found to be significant risk factors for adverse birth outcomes. Asian and Black women had 1.4–2.7 times the odds of LBW compared to White women (p < 0.01). Black women had increased odds of stillbirth (OR : 1.75, p = 0.017) and Asian women had increased odds of neonatal death (OR : 1.90, p < 0.001). The odds of LBW (OR : 3.3), premature birth (OR : 27.2), and neonatal death (OR : 5.6) were significantly increased for twins (p < 0.001). For women smoking at delivery, the odds of LBW (OR : 2.3), premature birth (OR : 1.5), and stillbirth (OR : 1.6) were significantly increased (p < 0.05). Deprivation, and/or financial and housing issues also increased the odds of adverse birth outcomes (p < 0.05).DiscussionThese findings underscore the importance of targeted interventions and support for at-risk populations to reduce adverse birth outcomes in vulnerable communities.